The Proposal of Co-Branding Strategy PT. XYZ and SAS in Automotive Sector in SPAIN Market to Increase PT. XYZ Reputation in International Market - Putra A, Freggy Griyatta; Nasution, Reza Ashari (The Indonesian Journal of Business Administration, 2012)
The development of the lubricant market in the Asia-Pacific, Africa, Middle East, and South America is an opportunity for PT.XYZ in the future. PT. XYZ wants to improve their brand image through co-branding with the SAS company as one of the local oil company in Spain. The study also analyzes the co-branding strategy through Joint Venture of PT. XYZ with SAS to improve the company's brand image in the international market. The conceptual framework of this research started from the goal of PT. XYZ to increase the brand image in the international market. The author analyzes the Joint Venture form between PT. XYZ with SAS and the alternatives that could be run by both companies thus this research recommends the most effective co-branding form for the PT. XYZ and SAS. The result of analysis of Joint Venture states that it is the most effective collaboration to increase the brand image of the PT. XYZ in the international market. However, the economic crisis in Spain made the Joint Venture form is more risky. Therefore, the author conducted an analysis of alternative forms of co-branding that can be run among Ingredient Branding, Product Creation, Promotion Joint, Joint Marketing, Branding and Joint by using Advantages and Disadvantages method. The result of the analysis states that the Ingredient Branding is the most effective alternative for current situation. In implementing the Ingredient Branding strategy, the research recommends the most appropriate alternative of Ingredient Branding strategy, canvas business model and implementation activity that can be run by PT. XYZ. Keywords: Co-branding, Joint Venture, Ingredient Branding.